Struktur Naratif Vladimir Propp Dalam Cerita “Rahwana Kasih Tak Sampai” Karya Rohmat Ilwanul Muslihin - Tedi Tahruri (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
There are so many romantic stories in this world that of course we are no strangers to these stories. Tragically the story of Romeo and Juliet, the death that ends the story of Tristan and Isolde, Layla Majnun whose grave is next to Qays, even though they are not married. And there are many more love stories in this world. Like this one story. It is Ravana's love for Sita in Ramayana. Ravana was the first son of Wisrawa and Dewi Sukesi who did forbidden things when Wisrawa taught Sastrajendra Hayuningrat Pangruwating Diyu. They did unexpected things when they discussed Sastrajendra Hayuningrat Pangruwating Diyu to the romance chapter. And finally a ten-faced giant was born, named Rahwana.